On the mappings preserving the Lyapunov stability of Takagi–Sugeno fuzzy systems - Denisenko, V. S.; Martynyuk, A. A.; Slyn'ko, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We propose a general principle of comparison for stability-preserving mappings and establish sufficient conditions of stability for the Takagi – Sugeno continuous fuzzy systems.